Legal Approaches to Cross-Border E-Commerce Consumer Protection in Indonesia, Singapore, and China - Firdausi, Anita; Prastyanti, Rina Arum (Yayasan Sinergi Kawula Muda, 2025)
This article examines consumer protection in cross-border e-commerce, focusing on Indonesia, Singapore, and China. The rapid growth of digital commerce across borders poses significant challenges for national legal systems in safeguarding consumer rights effectively. This study employs a normative juridical approach with qualitative-comparative analysis, exploring relevant legislation, policies, and law enforcement practices in the three countries. The findings reveal that Singapore has established the most comprehensive consumer protection legal framework, closely aligned with international standards. China utilizes a centralized regulatory model that emphasizes platform liability, resulting in stricter oversight of digital transactions. In contrast, Indonesia struggles with fragmented regulations, limited policy integration, and weak law enforcement, leading to less effective consumer protection in cross-border e-commerce. The study concludes that harmonizing international consumer protection standards and strengthening national law enforcement are crucial to addressing the challenges of cross-border e-commerce. Enhanced regulatory cooperation and improved consumer digital literacy are also necessary to ensure effective protection in digital markets.